2021
DOI: 10.1136/bmjopen-2021-054542
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health and Indigenous traditional midwives in southern Mexico: contextualisation of a scoping review

Abstract: ObjectivesCollate published evidence of factors that affect maternal health in Indigenous communities and contextualise the findings with stakeholder perspectives in the Mexican State of Guerrero.DesignScoping review and stakeholder fuzzy cognitive mapping.Inclusion and exclusionThe scoping review included empirical studies (quantitative, qualitative or mixed methods) that addressed maternal health issues among Indigenous communities in the Americas and reported on the role or influence of traditional midwives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Last but not least, we found no eligible studies on traditional and Indigenous self-care practices. While important qualitative research has been conducted on this topic,39 40 we hypothesise that there is a relative lack of studies exploring the health effects of these types of self-care practices. Future research on these topics could also provide new opportunities for improving cultural safety of maternity care services.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, we found no eligible studies on traditional and Indigenous self-care practices. While important qualitative research has been conducted on this topic,39 40 we hypothesise that there is a relative lack of studies exploring the health effects of these types of self-care practices. Future research on these topics could also provide new opportunities for improving cultural safety of maternity care services.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis will give the knowledge of adolescent girls and boys at least equal weight to that of other stakeholders. We will compare maps of different stakeholder groups and maps from stakeholder groups with the map from the scoping review [ 62 ]. Causes of adverse ASRH outcomes identified on the maps will inform the contextualization of the survey instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Supported by a specialist librarian, we will conduct a scoping review of quantitative and qualitative studies of factors associated with ASRH outcomes in low- and middle-income countries. In addition to a standard reporting of the review, we will create a fuzzy cognitive map (see as follows) of factors related to ASRH outcomes, marking the strength of associations as odds ratios or regression coefficients, and compare the literature map with stakeholder-created maps [ 62 , 64 , 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, westernized forms of regulation and standardization are not inclusive and disregard accumulated knowledge from Indigenous midwifery practices. For example, a recent study exploring maternal health and midwifery in Southern Mexico demonstrated that western health institutions and practices created culturally unsafe care for birthing families (Sarmiento et al 2021). This was evidenced by negative attitudes toward traditional midwifery, preference for colonial languages and worldviews, and a general disdain for Indigenous culture.…”
Section: Well-being In the Midwifery Profession: Toward A Contextuali...mentioning
confidence: 99%
“…While it might be expected that most research would focus on work-related determinants of midwives' well-being-given that being a midwife is, after all, a form of paid work-we posit that the almost exclusive focus on work-related factors stems from a false assumption: namely, that other aspects of midwives' lives are less important to their well-being. As discussed earlier, midwifery is a gendered, medicalized, and colonized profession (Clesse et al 2018;Kemp et al 2021;Sarmiento et al 2021). Therefore, the assumption that proximal work-related antecedents are the primary factors shaping midwives' well-being discounts the importance of broader structural elements such as gender, culture, and labor legislation.…”
Section: Work-related Factors Primarily Shape Midwives' Well-beingmentioning
confidence: 99%